Impact of the coronavirus on healh professionals: the portrait of Macaé (Research, Society and Development, 2020)
Coronavírus is part of a large group of viruses that cause respiratory infections that have important impacts on the health of healthcare professionals. Objective: to describe the profile of assistance to health professionals suspected of covid-19 in the city of Macaé in the firts two months of implementation of the Coronavirus Screening Center. Method: it constitutes a qualitative study with an analysis of the database of the Macaé Coronavírus Screening Center, created by the municipal epidemiological surveillance to monitor suspected cases of covid-19 in health professionals in the municipality. Result: 1065 visits to health professionals for covid-19 were recorded, 21% of cases confirmed. The most notified categories were nursing assistants and technicians, nurses, followed by doctors and others professionals. Most of the notifications occurred in the public network, with the absence of information on protective factors against the disease. Conclusion: The study contributed to the understanding of the covid-19 scenario in health professionals in the pandemic for the redirection of work by identifying the weaknesses of the service.